Modernizing Blood Donation Policies: Challenging the Lifetime Ban on MSM and Transgender Individuals - Upadhyay , N; Chatterjee, P (Journal of Indian Academy of Forensic Medicine, 2024)
This article will shed light on a medico-legal issue where MSM (male sex with male) are life-time debarred from blood donation on the basis of suspicion that they can have HIV infection and can transmit the same to others through blood transfusion. In the 1980s, acquired immunodeficiency syndrome, popularly known as AIDS, left the world in fear and stigma. Until 1980, the number 1 of cases and causes of HIV were greatly unknown. During the 1980s, HIV reached around 5 continents (Australia, South America, North America, Europe, and Africa), covering around 1 million people affected by it. The early detection of HIV was linked to males who have sex with males (MSM). In 1982, many gay men in southern California were diagnosed with HIV, and because of this, HIV at that time was called gay-related immune 2 2 deficiency. In 1982, CDC used the term “AIDS”. According to the WHO, around 39 million people around the 3 globe will be living with HIV by 2022. National Blood Transfusion Guidelines 2017 under Point 51 prohibits the donation of blood by people who have male-to-male sex and are 4 transgender. The same kind of prohibition on blood donation can also be seen in the USA.